Oscillatory pallidal local field potential activity inversely correlates with limb dyskinesias in Parkinson's disease. - Silberstein, P; Oliviero, A; Di Lazzaro, V; Insola, A; Mazzone, P; Brown, P (2005)
Levodopa induced dyskinesias (LIDs) are poorly understood and yet are a major cause of disability in Parkinson's disease (PD). The activity of neurons in the basal ganglia of patients with PD tends to be strongly synchronized at frequencies under 30 Hz, leading to oscillatory local field potentials (LFPs). As dopaminergic therapy acutely suppresses this synchronization, we investigated whether this suppression may contribute to LIDs. Accordingly, we sought an inverse correlation between oscillatory synchronization and dyskinesia activity across time. To this end, we recorded pallidal LFPs in two Parkinsonian subjects exhibiting LIDs following surgery for deep brain stimulation. We correlated LFP power with simultaneously recorded EMG from the dyskinetic contralateral upper limb. We found highly significant inverse correlations between the oscillatory LFP activity under 30 Hz and dyskinetic EMG (maximum r = -0.65, P < 0.001 and r = -0.33, P < 0.001 for activities over 13-30 Hz in each subject). The inverse relationship between oscillatory pallidal LFP activity and dyskinetic EMG was maintained over time periods of a few seconds and was focal. This observation links the suppression of oscillatory synchronization in the pallidum with dyskinetic muscle activity in PD.